Physiological Factors in the Regulation of Alkaline Phosphatase Synthesis in Escherichia coli - Wilkins, Adam S. (1972)
Alkaline phosphatase is induced in excess phosphate media by starvation either for pyrimidines or for guanine. Induction is observed both during starvation, after a lag period, and following a period of starvation. Induction is not caused by a lowering of the internal orthophosphate pool, but is linked to alterations in the levels of the nucleotide pools. Experiments with purine-requiring mutants suggest that phosphatase is induced in wild-type strains by an adenine nucleotide. Mutations in the phoR gene can produce differential responses to the different starvation regimes.